Health in Prisons: the speaking nursing workers - Fernanda de Jesus dos Santos Nanda (Universidad de Alicante, 2015)
Objective: To analyze the health care provided to persons under confinement in the penitentiary system in the view of nursing. Methodology: An exploratory study, a qualitative approach to analyze the discussion of participants, from the guiding question: How do the nursing staff perceive the health care offered in the prison system? Data collection was performed through recorded interviews with the signing of terms of free and informed consent, conducted in April 2014, with 21 nursing staff of the penitentiary complex Maceió-AL, as approved by the Ethics Committee and research Platform UFAL via Brazil, and by CAAE No 25016814.6.0000.5013, receiving assent to its publication as protocol 560 840. Results: From the analysis of the interviews, three categories emerged: Many difficulties, some privileges; Stress, fear and involvement; Institutional force-health attention. Conclusion: This study contributes to the knowledge on the topic in question, and the debate on health care offered in the prison system in order to improve service delivery and care persons deprived of liberty.